1989
DOI: 10.1016/0022-1910(89)90089-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quantity and quality of diet nitrogen on the growth, efficiency of food utilization, nitrogen budget, and metabolic rate of fifth-instar Spodoptera eridania larvae (Lepidoptera: Noctuidae)

Abstract: Abstract-Relative growth rate and relative nitrogen accumulation rate for fifth-instar Spodoptera eridania larvae vary less than 20% on artificial diets in which protein content varies more than 250%, due to compensatory adjustments in consumption rate and changes in efficiencies of food and nitrogen utilization. The substitution of zein for two-thirds of the casein in a diet containing 26.0% protein results in a 25% decrease in both relative growth and nitrogen accumulation rates, due to reduced values of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
2
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 35 publications
7
101
2
2
Order By: Relevance
“…Protein repair and cellular maintenance occupy a larger share of the overall N budget at high temperatures, yielding less excess N available for growth after accounting for basic cellular processes . Indeed, respiration and metabolic rates were highest for caterpillars reared on low-N diets arising from the greater difficulty of processing diets rich in non-labile carbohydrates (Martin & Van't Hof 1988;Karowe & Martin 1989). However, increased cellular respiration rates do not generally translate into increased metabolic N turnover.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Protein repair and cellular maintenance occupy a larger share of the overall N budget at high temperatures, yielding less excess N available for growth after accounting for basic cellular processes . Indeed, respiration and metabolic rates were highest for caterpillars reared on low-N diets arising from the greater difficulty of processing diets rich in non-labile carbohydrates (Martin & Van't Hof 1988;Karowe & Martin 1989). However, increased cellular respiration rates do not generally translate into increased metabolic N turnover.…”
Section: Discussionmentioning
confidence: 99%
“…We created three diets of varying quality by replacing casein in the standard lepidopteran diet with non-digestible cellulose to maintain constant water content. This is a standard method of generating artificial diets, and previous work demonstrated that N assimilation efficiency does not vary with casein concentrations in this species (Karowe & Martin 1989). We determined diet N concentrations of each diet via elemental analysis using 8 replicate subsamples from each diet (FlashEA 1112 Series CHN analyzer, Thermo Electron Corporation; Table 3.1).…”
Section: We Conducted All Feeding Experiments At the Smithsonian Envimentioning
confidence: 99%
See 3 more Smart Citations